Peran Departemen Sumber Daya Manusia dalam Perencanaan, Rekrutmen Dan Seleksi Untuk Mendapatkan SDM Unggul - Arfin, Antoni Ludfi (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this research is to analyze the role of human resources department in conducting HR planning, recruitment, and selection to meet the needs of the best employee. This study is literature review from related manpower planning, recruitment, and selection. The literatures were collected from 50 journal articles from 2000 to 2020. The results showed that the human resources department has a role in HR planning, recruit, and select the human resources needed. The results explain that the human resources department has a role in formulating and determining the HR planning, source of candidate, selection methods, and stages of selection. HR department has a role in the process of determining selection strategies based on company planning. The role of the HR department is very important in the process of acquiring superior HR with a mechanism or system to selection the best employee.